2020
DOI: 10.3389/fnins.2020.571210
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cerebellar-Cerebral Circuits in Patients With Type 2 Diabetes Mellitus

Abstract: The role of the cerebellum in type 2 diabetes mellitus (T2DM) has been receiving increased attention. However, the functional connectivity (FC) between the cerebellar subregions and the cerebral cortex has not been investigated in T2DM. Therefore, the purpose of this study was to investigate cerebellar-cerebral FC and the relationship between FC and clinical/cognitive variables in patients with T2DM. A total of 34 patients with T2DM and 30 healthy controls were recruited for this study to receive a neuropsycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Previous laboratory studies found the association between motor deficits and the cerebellar damage in diabetic rats (Sherin et al, 2010;Nagayach et al, 2014). The cerebellum dysfunctions also related to impaired cognition in patients with T2DM as structural and functional connectivity alterations were found in the cerebellar and cerebrocerebellar circuits (Fang et al, 2017;Zhang D. et al, 2020). The hyperactivity in the cerebellum might be a recruitment of additional neural resources to compensate for loss of cognitive function in the cerebral regions (Xia et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Previous laboratory studies found the association between motor deficits and the cerebellar damage in diabetic rats (Sherin et al, 2010;Nagayach et al, 2014). The cerebellum dysfunctions also related to impaired cognition in patients with T2DM as structural and functional connectivity alterations were found in the cerebellar and cerebrocerebellar circuits (Fang et al, 2017;Zhang D. et al, 2020). The hyperactivity in the cerebellum might be a recruitment of additional neural resources to compensate for loss of cognitive function in the cerebral regions (Xia et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…The cerebellum is connected to the prefrontal cortex and other non-motor cortical regions via projecting fibers and synapses (29). In a recent functional neuroimaging study, patients with type 2 diabetes showed decreased functional connectivity between the cerebellum and dorsolateral prefrontal cortex compared to normal controls (42). Atrophic changes of related structures in diabetes are linked to gait disturbance even in patients without diabetic peripheral neuropathy (36).…”
Section: Discussionmentioning
confidence: 99%
“…Previous cross-sectional magnetic resonance imaging (MRI) studies have consistently reported associations between T2DM and reduced global brain volume ( Wardlaw et al, 2013 ; Weinstein et al, 2015 ; Zhang et al, 2020 ; Adachi et al, 2021 ; Hyung et al, 2021 ). In addition, microvascular lesions and neurodegeneration markers related to Alzheimer’s disease (AD) have been associated with T2DM ( Tan et al, 2019 ; Zhang et al, 2019 ; Wu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%